The role of partner influence in contraceptive adoption, discontinuation, and switching in a nationally representative cohort of Ugandan women. - Dana O Sarnak; Shannon N Wood; Linnea A Zimmerman; Celia Karp; Fredrick Makumbi; Simon P S Kibira; Caroline Moreau (PLoS ONE)
Background Understanding contraceptive use dynamics is critical to addressing unmet need for contraception. Despite evidence that male partners may influence contraceptive decision-making, few studies have prospectively examined the supportive ways that men influence women's contraceptive use and continuation. Objective This study sought to understand the predictive effect of partner influence, defined as partner's fertility intentions and support for contraception, and discussions about avoiding pregnancy prior to contraceptive use, on contraceptive use dynamics (continuation, discontinuation, switching, adoption) over a one-year period. Methods This study uses nationally representative longitudinal data of Ugandan women aged 15-49 collected in 2018-2019 (n = 4,288 women baseline; n = 2,755 women one-year follow-up). Two analytic sub-samples of women in union and in need of contraception at baseline were used (n = 618 contraceptive users at baseline for discontinuation/switching analysis; n = 687 contraceptive non-users at baseline for adoption analysis). Primary dependent variables encompassed contraceptive use dynamics (continuation, discontinuation, switching, and adoption); three independent variables assessed partner influence. For each sub-sample, bivariate associations explored differences in sociodemographic and partner influences by contraceptive dynamics. Multinomial regression models were used to examine discontinuation and switching for contraceptive users at baseline; logistic regression identified predictors of contraceptive adoption among non-users at baseline. Results Among users at baseline, 26.3% of women switched methods and 31.5% discontinued contraceptive use by follow-up. Multinomial logistic regression, adjusting for women's characteristics, indicated the relative risk of contraceptive discontinuation doubled when women did not discuss pregnancy avoidance with their partner prior to contraceptive use. Partner influence was not related to method switching. Among non-users at baseline, partner support for future contraceptive use was associated with nearly three-fold increased odds of contraceptive adoption. Significance These results highlight the potentially supportive role of male partners in contraceptive adoption. Future research is encouraged to elucidate the complex pathways between couple-based decision-making and contraceptive dynamics through further prospective studies.